Pre‐fall prognostics, prevention and management of frailty in geriatrics: A personalized intelligent system approach (ALL‐FrAAgile): Implementation of person‐centered care. (7th December 2020) - Marinescu, Mihaela; Bartolome, Inaki; Marzan, Mircea; Mashayekhi, Kaveh; Spiru, Luiza
Abstract: Context: Frailty is a clinical state in which there is an increase in an individual's vulnerability for developing an increased dependency and/or mortality when exposed to a stressor". Frailty can occur in 15% of adults aged 65 years and over as the result of a variety of medical and socio‐demographic conditions such as living alone, depression, polypharmacy, malnutrition or sedentary lifestyle, etc. Even small stressors may increase the risk of developing significant health complications such as falls, dependency and hospitalizations. Nevertheless this state can be reversed through personalized intervention. So screening, evaluation and management are highly important. Objectives: Frailty detection and prevention. Methods: The FrAAgile is an ICT based personalized Ambient Assisted Living (ALL) intelligent system aimed at pre‐fall prognostics, identification, prevention and management of physical and mental frailty and multimorbidity and transition to robust health status. A personalized intelligent role‐based service is offered to access and improve the physical and the mental state of the individual through physical and cognition‐enhancing games based exercises. Intelligent system applications accessing the individual's behavior, cognition, mood, agility, onset/lack of outside activities, balance, gate etc. to define a personalized role for that particular person to improve his/her physical and mental condition avoiding fall incidents due to frailty. This approach can be implemented and offered as a service directly to an individual user or to his/her informal and formal caregivers. Results: During the CO‐creation phase, more than ninety End‐Users in Cyprus, Spain, Switzerland and Romania sites are identified and started to be recruited since Jan 2020. The ICT architecture of the project has been defined, considering required hardware, web‐connection, cloud database, data collection modules, video, and game applications and libraries. Conclusion: The mild cognitive impairment individuals (MCI) would be accompanied across three phases of pre‐trial pilot lab‐testing, adaptation, and optimization, which leads finally to field trails. The main focus of the role‐based intervention aims to prevent clinical frailty and falls incidence through augmenting physical and mental health condition considering a holistic personalized view of the individual lifestyle and condition (EU AAL‐frAAgiLe project, Active Assisted Living, Ageing Well in the Digital World, aal‐2018‐5‐152‐CP).